Starting from scratch: prevalence, methods, and functions of non-suicidal self-injury among refugee minors in Belgium - Sarah Verroken; Chris Schotte; Ilse Derluyn; Imke Baetens (BMC, 2018)
Abstract Background As many refugee minors have gone/go through stressful life experiences and uncertainty, one might expect mental health issues, including self-injury. However, literature on non-suicidal self-injury (NSSI) in refugee minors is scarce. This study explores the prevalence, methods, and functions of NSSI in refugee minors in Belgium, and compares research results to the existing literature on NSSI in Western adolescents. Methods Data were obtained from 121 refugee minors (mean age = 16.12, SD = 1.23; range 14-18 years) through schools located in the Flemish and Brussels-Capital regions of Belgium. The sample consists of 39.7% girls and 60.3% boys. Self-report questionnaires were used to explore socio-economic data, NSSI behaviour (e.g. The Brief Non-Suicidal Self-injury Assessment Tool; BNNSI-AT) and emotional and behavioural difficulties (The Strengths and Difficulties Questionnaire; SDQ). Non-parametric Chi square tests were used for statistical comparisons of the obtained data as well as independent-sample t-tests and Fisher's exact tests. Results Results show a lifetime NSSI prevalence rate of 17.4%. Being accompanied or not, having both parents around, or living in an asylum centre did not influence NSSI prevalence. An average of 2.65 methods of NSSI was applied (SD = 2.50; range 1-9). The mean number of functions per person was six (SD = 4.97, range 0-16), with automatic functions reported the most. The data do point towards a greater psychological strain, with 68.4% reporting more than five acts of NSSI. Results of the SDQ's Total Difficulties Scale and, more specifically, of the Emotional Problems, Conduct Problems, Peer Problems and Impact Scales indicate a substantial risk of clinically significant problems within the NSSI group. The Peer Problems and Impact Scales also point towards a high risk for suicidality amongst self-injuring refugees. Conclusions Prevalence rates, methods and functions are comparable to Western samples. However, the higher incidence of the NSSI and the results on the SDQ also emphasise the vulnerability of refugee minors.